1996
DOI: 10.1056/nejm199604253341704
|View full text |Cite
|
Sign up to set email alerts
|

Improvement in Pulmonary Function and Elastic Recoil after Lung-Reduction Surgery for Diffuse Emphysema

Abstract: Lung-reduction surgery can produce increases in the elastic recoil of the lung in patients with diffuse emphysema, leading to short-term improvement in dyspnea and exercise tolerance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
206
0
4

Year Published

1998
1998
2010
2010

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 438 publications
(221 citation statements)
references
References 23 publications
11
206
0
4
Order By: Relevance
“…Regarding TLC25, however, its definition could lead to an artificial overestimation as compared to "voluntary TLC". Indeed, the detrimental effects of hyperinflation on inspiratory-muscle efficiency lead to the inability to develop a transpulmonary pressure in emphysematous subjects as high as that in normal subjects [15]. However, if TLC increased by a 20% margin as is observed in patients, the RV/TLC would still only approach 39%, which remains very low.…”
Section: Discussionmentioning
confidence: 98%
“…Regarding TLC25, however, its definition could lead to an artificial overestimation as compared to "voluntary TLC". Indeed, the detrimental effects of hyperinflation on inspiratory-muscle efficiency lead to the inability to develop a transpulmonary pressure in emphysematous subjects as high as that in normal subjects [15]. However, if TLC increased by a 20% margin as is observed in patients, the RV/TLC would still only approach 39%, which remains very low.…”
Section: Discussionmentioning
confidence: 98%
“…Early physiologic studies of LVRS focused on increased elastic recoil and decreased airway resistance (13)(14)(15)(16)(17). For example, Gelb and coworkers showed that LVRS increased elastic recoil at a given lung volume (13,14).…”
Section: Increased Lung Elastic Recoilmentioning
confidence: 99%
“…reduced airway resistance). In contrast to the situation following lung volume reduction surgery [13], acute BD administration was not associated with increased elastic lung recoil pressure and is not, therefore, likely to affect the statically determined relaxation volume of the respiratory system. The main impact is therefore on the dynamically determined resting EELV through pharmacological manipulation of resistance in the airways upstream from the flow-limiting segments [14,15].…”
mentioning
confidence: 63%